Calculation of Hazard Indicators for Some Materials Used in Construction and Selected from the Iraqi Market - A.Essa, Saad; H. Mahmood, Yaseen; K. Mohammad, Kareem (Al-Nahrain Journal of Science, 2024)
The main objective of this study is to measure the levels of radioactivity in certain construction material samples by quantifying the amounts of natural radionuclides (238U, 232Th, 40K) and 137Sc using gamma-ray spectroscopy with a High Purity Germanium (HPGe) detector. The selected samples were collected and examined to ascertain the mean quantities of radionuclides present. Subsequently, these findings were juxtaposed with global benchmarks for additional examination. The efficiency results unveiled a spectrum of concentrations for different radionuclides, encompassing 238U with a concentration range of (2.53 - 8.2 Bq/kg) and an average concentration of (4.93 Bq/kg). Similarly, the concentration of 232Th ranged from (0.655 - 3.45 Bq/kg), with an average concentration of (1.74 Bq/kg). The radionuclide 40k exhibited a concentration range of (3.5 -1500 Bq/kg), with an average value of (386.4 Bq/kg). Furthermore, 137Sc displayed a concentration range of (0.51-0.22 Bq/kg) with an average concentration of (0.53 Bq/kg). The radium equivalent concentration was determined to be (40.45 Bq/kg), whereas the absorbed dosage was measured at (18.67 nGy/h). The external hazard index (Hout) was measured to equal (0.11 mSv/y), whereas the internal hazard index (Hin) was determined to be (0.17 mSv/y). Furthermore, the annual equivalent effective dose (AEDEout) was calculated to be (0.09 mSv/year). The annual dosage of (AEDEin) was determined to be (0.02 mSv/year). The gamma radiation index, denoted as Iγ, was determined to be (0.28 Bq/kg). The study results imply that the amounts of radionuclides fall within the defined normal limits worldwide, indicating that the natural radioactivity levels are within the internationally acceptable range. Quantification of both natural and artificial radioactivity in specific building materials employed in constructing dwellings inside Salah Al-Din Governorate. A selection of seven distinct models was made. (Plaster, Bork, and Dust). The concentration of gamma-ray-emitting radionuclides in both the uranium-radium and thorium series, as well as 40K and 137Sc, was measured using a high-purity germanium (HpGe) detector. Subsequently, the spectrum underwent analysis for 3600 seconds. The concentrations of the radionuclides being investigated were determined to be as follows: The mean concentrations of 238U range from (2.53 - 8.2 Bq/kg), while for 232Th the range from (0.65 to 3.45 Bq/kg). The concentrations of potassium 40K range from (3.5 to 1500 Bq/kg), and for 137 Sc the range from 0.51 to 0.22 Bq/kg.